Acute Posterior Multifocal Placoid Pigment Epitheliopathy Complicated by Fatal Cerebral Vasculitis. Issue 2 (June 2019) - Maamari, Robi N.; Stunkel, Leanne; Kung, Nathan H.; Ferguson, Cole J.; Tanabe, Jody; Schmidt, Robert E.; Dahiya, Sonika; Dhand, Amar; Van Stavern, Gregory P.; Rajagopal, Rithwick; Harocopos, George J.
Abstract : Abstract: A 21-year-old man experienced unilateral vision loss associated with multiple atrophic chorioretinal lesions. He was treated for a presumptive diagnosis of acute retinal necrosis, but his vision did not improve with antiviral therapy. Over the course of several weeks, his symptoms progressed to involve both eyes. The fellow eye showed characteristic yellow-white placoid lesions, prompting treatment with oral corticosteroids for acute posterior multifocal placoid pigment epitheliopathy (APMPPE). Despite high-dose therapy with prednisone 80 mg daily, the patient developed the acute onset of mental status changes within the next several days. Neuroimaging revealed multifocal large-vessel strokes associated with cerebral edema; these infarcts led to herniation and death. Postmortem histopathologic examination confirmed granulomatous inflammation in both ocular and cerebral vasculatures. Together with findings from multimodal imaging obtained throughout this patient's clinical course, our findings support the notion that granulomatous choroiditis is the mechanism of the ocular lesions seen in APMPPE. This granulomatous inflammation can also affect cerebral vessels, leading to strokes.